The Components of Cooperation Network of the Kalasin Municipality Elderly School - Srisontisuk, Somsak; Aimimtham, Sukanya; Yokun, Anongnath; Dononbao, Aphiradee; Deeod, Pongmanut (Dhammathas Academic Journal, 2023)
The purpose of this research was 1) to study achievement condition of elderly people’s school participation management of Kalasin municipality and 2) to analyze elements on participation network for health activities of elderly people’s school of Kalasin municipality in a qualitative analysis form by studying about participation network and key elements which leads to success in the establishment of elderly people’s school of Kalasin municipality. From the study and data analysis from primary documents, in-depth interview, and focus group of elderly school stakeholders and took part in activities with three different groups of Kalasin Municipality Elderly Schools to develop a network management model for Kalasin Municipality Elderly Schools. The results revealed that: 1. Network management should be the highest priority to be realized to succeed in elderly people’s school establishment. Realizing the importance of elderly people’s society for all section, leadership of the administrator, and participation establishment are important condition to lead the organization succeed in the elderly people’s school management. 2. The elements for participation network for health activities of elderly people’s school that can bring the organization to succeed shall compose of 4 factors which are 1) realizing their roles and responsibilities, 2) participation, 3) creation of reliability, 4) communication among the participation networks. If both two mentioned operations can be proceeded, they must be operated in a coordinated manner to succeed in the establishment of health activities network of the elderly people’s school.